Seleksi Jagung Inbrida dengan Marka Molekuler dan Toleransinya terhadap Kekeringan dan Nitrogen Rendah - Efendi, Roy; Musa, Yunus; Bdr, M. Farid; Rahim, M. Danial; Azrai, M.; Pabendon, Marcia (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
Information on genetic diversity, homozygosity, drought stress and low N tolerance of maize inbred line are useful for parental selection in developing maize varieties tolerant to drought and low N. The objectives of this study were (a) selection for homozygoes lines and analysis of genetic diversity among 51 maize inbred lines applying simple sequence repeats (SSRs) using thirty six markers (b) selection for inbred lines (homozygosity over 80%) for drought and low nitrogen (N) tolerance. Experiment was conducted using split-split plots design with three replications. Water treatments were as the main plots (well-watered and drought stress conditions), subplots were nitrogen fertilization at rate of 75 and 150 kg N/ha and the sub-sub plots were 51 inbred lines. The results showed that there were broad ranges of genetic variability among inbred lines with genetic similarity coefficient values ranging from 0.22 to 0.87 and polymorphism information content average was 0.57. Thirty inbreds having homozygosity over 80% were spread into six heterotic groups. Drought tolerance inbreds were in heterotic groups C and F, namely DTPYC9-F46-3-9-1-1-B and 1044-30, the drought medium tolerance in heterotic group A and B, namely CML 161/NEI 9008 and MR 14. Inbred for low-N fertility tolerance was in the heterotic group D namely G20133077, while medium tolerance to low-N fertility inbreds were in heterotic group A, B, C, D, and F, and they were CML 161/NEI 9008, CY 11, CY 15, CY 6, CLRCY039, Nei9008, DTPYC9-F46-1-2-1-2-B, G2013627, G2013649, 1044-30. Inbreds tolerance to both medium drought and to low-N fertility were in heterotic group C and F they were DTPYC9-F46-1-2-1-2-B and 1044-30. Inbred lines of maize tolerant to drought and to low-N fertility can be used as parent to develop hybrid or synthetic varieties, posessing stress tolerances, by cross recombination between heterotic groups.